Penguatan Literasi Penulisan Artikel Ilmiah Pada Kelompok Ilmiah Remaja SMAN 5 Bandar Lampung Menuju Publikasi Jurnal Nasional - Susanti Sundari; Thabita Carolina; David Saputra (LPPM Universitas 17 Agustus 1945 Semarang, 2022)
Activities in improving literacy of scientific article writing by the KIR of SMAN 5 Bandar Lampung aims to encourage students in scientific article writing activities towards journal publications which so far have not been carried out, because writing skills are not obtained naturally through the process of practicing and continuing to learn. The training methods carried out include questionnaires, brainstorming, introduction of several writing tools, systematic deepening of writing good scientific articles, and evaluation. The result of this activity is an increase in the understanding and motivation of students and coaches about the importance of publishing articles that have a good impact on themselves, school and community. So three articles that are ready to be written and published in journals, a coaching clinic series that is needed is assistance to encourage the quantity and improve the quality of writing by direct practice.